Ceftazidime-avibactam resistance determination in carbapenem-resistant Klebsiella pneumoniae infections before its use in practice - Oya Özlem Eren-Kutsoylu; Hacer Ceylan-Çimendağ; Ayşe Nur Sari-Kaygisiz; Elif Seren Tanriverdi; Özgen Alpay Özbek; Ibrahim Mehmet Ali Öktem; Barış Otlu; Vildan Avkan-Oğuz (Journal of Infection in Developing Countries)
Introduction: To ensure the appropriate usage of ceftazidime-avibactam (CAZ-AVI), recently introduced in our hospital, we aimed to determine susceptibility rates, enzyme analysis, and clonal relationship among strains, together with clinical data.